A POSTCOLONIAL STUDY OF CULTURAL HYBRIDITY IN THE CHARACTER OF NANCY OBI IN CHINUA ACHEBE’S “DEAD MEN’S PATH” - Hafiz Muhammad Jamil (International Journal of Contemporary Issues in Social Sciences, 2024)
The paper deals with the intricate layers of cultural hybridity as portrayed in Chinua Achebe's short story "Dead Men's Path," employing Homi Bhabha's post-colonial theories as a lens for analysis. Bhabha's conceptual framework, rooted in the notion of "third space" and the dynamics of mimicry and ambivalence, provides a nuanced understanding of how cultural identities intersect and evolve in the postcolonial context. The study investigates how Bhabha's theories illuminate the nuances of cultural hybridity within the narrative, examining the characters' negotiations of identity and the clash between traditional and colonial values. By scrutinizing the transformative impact of Nancy Obi’s garden or Michael Obi’s village school, the paper aims to unravel the creation of new cultural spaces and the emergence of power struggles within the community or new, modern ways are better than the traditions of the villagers in Nigeria. Through a deep textual analysis of the short story, the study seeks to contribute to the broader discourse on postcolonial literature and studies on cultural hybridity. While bridging the gap between theory and narrative, it endeavors to shed light on the ways in which Bhabha's conceptual tools can enrich our understanding of the complex dynamics inherent in the representation of cultural hybridity within the postcolonial literary landscape.